Challenges and opportunities in higher education diplomacy of World Class Universities in Indonesia: analysing the network environment of public diplomacy - Ayu Anastasya Rachman; R. Dudy Heryadi; Junita Budi Rachman; Yanyan Mochamad Yani (Cogent Social Sciences, 2024)
This paper aims to investigate Indonesia’s aspiring World Class University, challenges and opportunities when conducting public diplomacy. By analysing the network environment of public diplomacy, this study seeks to shed light on the dynamics and intricacies of diplomatic engagement between Indonesian WCUs and national/international stakeholders. A qualitative methodology was employed, utilizing in-depth semi-structured interviews with 12 informants who hold leadership positions at their respective universities. The data collected from these interviews were rigorously analysed using source triangulation techniques. Complementing this qualitative approach, the study also undertakes a detailed examination of the demographic characteristics and responses from a survey administered to 120 international students across Universitas Indonesia (UI), Universitas Gadjah Mada (UGM), and Institut Teknologi Bandung (ITB) from July to October 2022. The study unveiled that knowledge transfer activities exert a substantial influence on all World Class University (WCU) Times Higher Education (THE) indicators, including Industry Income, Teaching, Research, Citations, and International Outlook. It also revealed a significant gender disparity among international students, with males predominating. Furthermore, the survey highlighted UGM as the most frequent choice among international students, indicating institutional preferences and potential areas for strategic internationalisation efforts. The findings suggest that universities should enhance their academic exchange and partnerships, to improve their global rankings and appeal to international students. Institutions need to address gender disparities in their international student populations by implementing targeted recruitment strategies. Lastly, universities less chosen by international students could analyse UGM’s practices to adopt effective strategies for attracting a more diverse international student body.